The Anicteric Giant: A Rare Case of Giant Choledocholithiasis and Multiple Cholelithiasis Presenting with Paradoxically Normal Bilirubin Profiles - Sujek Miko Eka Putra; Mochammad Riskie Aditya Putra (HM Publisher, 2026)
Background: Giant choledocholithiasis, defined as common bile duct (CBD) calculi exceeding 15 mm, typically presents with Charcot’s triad or marked biochemical cholestasis. The phenomenon of silent or anicteric giant stones remains a dangerous diagnostic blind spot. We present a rare case of a massive biliary stone burden presenting with paradoxically normal bilirubin and liver enzyme profiles, challenging standard screening algorithms. Case presentation: A 61-year-old female presented with a 12-month history of intermittent epigastric pain and nausea, initially misdiagnosed as gastritis. Despite the chronicity, she denied jaundice or fever. Biochemical analysis revealed a Total Bilirubin of 0.39 mg/dL (Reference: 0.1–1.2 mg/dL) and normal gamma-glutamyl transferase (GGT) levels, indicating an absence of biochemical obstruction. Magnetic resonance cholangiopancreatography (MRCP) identified multiple cholelithiasis and a solitary giant CBD stone. Intraoperative exploration confirmed a CBD dilated to 22 mm containing a calculus measuring 28 mm × 22 mm. Due to the massive ductal dilation and risk of recurrent stasis, the patient underwent a retrograde cholecystectomy followed by biliary reconstruction via Roux-en-Y choledochojejunostomy. Conclusion: Giant choledocholithiasis can exist in a silent phase due to ductal compliance and the ball-valve mechanism, rendering bilirubin an unreliable screening tool. This case underscores the necessity of cross-sectional imaging in chronic abdominal pain, even when biochemical markers are normal. Roux-en-Y reconstruction remains the definitive management for giant stones in significantly dilated ducts to prevent recurrence and sump syndrome.